Preventing and Responding to Dissent: The Observational Challenges of Explaining Strategic Repression – CORRIGENDUM. - RITTER, EMILY HENCKEN; MONROE, COURTENAY R. (American Political Science Review, 2024)
The document is a correction notice for an article titled "Preventing and Responding to Dissent: The Observational Challenges of Explaining Strategic Repression." The authors acknowledge two statistical errors in the article and provide the corrected results in Table 1. The errors were related to the operationalization of the dependent variable, Mobilized Dissent, and the results were estimated using the incorrect operationalization. However, the correction does not significantly change the estimates or affect the substantive conclusions of the article. The revised results and replication files are available for further reference. The given text provides model statistics and revised results for a study on the effect of mobilized dissent on state repression in US state-days. The authors discovered a coding error in their data on conflict and rainfall in the United States, which they have corrected. The revision to Table 2 does not significantly change the estimates or affect the substantive conclusions of the study. The revised results are available for replication on the APSR Dataverse.